Forms of Health System Fragmentation During Conflict: The Case of Yemen - Dureab, Fekri; Hussain, Taha; Sheikh, Rashad; Al-Dheeb, Najwa; Al-Awlaqi, Sameh; Jahn, Albrecht (Frontiers in Public Health, 2021)
The continuous and protracted conflict in Yemen has evolved into the worst humanitarian situation in modern history. All public structures in the country, including the health system and its basic functions, have been under tremendous pressures. One of the key obstacles to improve the health outcomes in Yemen is fragmentation of the health system. This study aims at exploring and documenting the forms of health system fragmentation in humanitarian and conflict-affected contexts by studying Yemen as a case study. We collected national qualitative data from key informants through in-depth interviews. A pool of respondents was identified from the Ministry of Public Health and Population, donors, and non-governmental organizations. Data were collected between May and June 2019. We interviewed eight key informants and reviewed national health policy documents, and references provided by key informants. Interviews were recorded, transcribed, and analyzed using qualitative content analysis. We further conducted a literature review to augment and triangulate the findings. Six themes emerged from our datasets and analyses, representing various forms of fragmentation: political, structural, inter-sectoral, financial, governance, and health agenda-related forms. Health system fragmentation in Yemen existed before the conflict eruption and has aggravated as the conflict evolves. The humanitarian situation and the collapsing health system enabled the influx of various national and international health actors. In conclusion, the protracted conflict and fragile situation in Yemen have accentuated the fragmentation of the health system. Addressing these fragmentations' forms by all health actors and building consensus on health system agenda are recommended. Health system analysis and in-depth study of fragmentation drivers in Yemen can be beneficial to build common ground and priorities to reduce health system fragmentation. Furthermore, capacity building of a health system is fundamental for the humanitarian development nexus, health system integration, and recovery efforts in the future.